OPTIMIZATION OF THE LAY UP SHOOT LEARNING RESULTS IN BASKETBALL GAME THROUGH MODIFIED LEARNING USING PLASTIC BALLS IN XI CLASS STUDENTS PRIVATE VOCATIONAL SCHOOL OF PAB 6 MEDAN YEAR 2018/2019 AJARAN - Andi Nur Abady; Liliana Puspa Sari; Pedomanta Keliat (Jurnal Ilmiah STOK Bina Guna Medan, 2020)
This study aims to determine the increase in lay ap shoot learning outcomes through the use of modified media in class XI students of PAB 6 Medan Private High School in 2018/2019. From the results of the preliminary data (pre-test) that has been done, it shows that the students' ability to do the lay-up technique is still low and this has an impact on student learning outcomes. This research uses Classroom Action Research (CAR) which can be analyzed. In this case the researcher analyzes the data by reducing the data and presenting the data in table form, so that the average grade and the percentage of learning completeness can be found. The samples in this study were students of class XI IPS SMA Private PAB 6 Medan in 2018/2019, totaling 17 people. , consisting of 3 male students and 14 female students. The results of the research in the first cycle showed that the learning outcomes of the lay-up shoot were (41%) students who completed their studies, and (59%) students who did not complete their studies. Overall student learning outcomes in doing the lay-up shoot technique in the first cycle reached (58.82%). In cycle II shows that the learning outcomes of the lay-up shot, namely (88%) students who complete their learning, and (12%) students who do not complete their learning and overall student learning outcomes in doing the lay-up shoot technique in cycle II reach (88 , 23%). This study concludes that the use of plastic ball modification media can provide a very large and significant contribution to the learning outcomes of shoot lay-ups in class XI IPS class students of PAB 6 Medan Private High School in 2018/2019.